2011
DOI: 10.1002/glia.21266
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a microglia phenotype supportive of remyelination

Abstract: In multiple sclerosis, endogenous oligodendrocyte precursor cells (OPCs) attempt to remyelinate areas of myelin damage. During disease progression, however, these attempts fail. It has been suggested that modulating the inflammatory environment of the lesion might provide a promising therapeutic approach to promote endogenous remyelination. Microglia are known to play a central role in neuroinflammatory processes. To investigate the microglia phenotype that supports remyelination, we performed genome-wide gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
270
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(295 citation statements)
references
References 74 publications
(75 reference statements)
19
270
0
2
Order By: Relevance
“…In this model, the vast majority of activated MPs are endogenous microglia, not peripheral macrophages (49)(50)(51)(52). At W4 of CPZ, proinflammatory MPs in the corpus callosum express the phagocytic marker CD11b and are responsible for the phagocytosis of myelin debris (53,54). This supportive action of MPs is an essential step for subsequent remyelination at W6 and W6 + W6 recovery (49,55).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the vast majority of activated MPs are endogenous microglia, not peripheral macrophages (49)(50)(51)(52). At W4 of CPZ, proinflammatory MPs in the corpus callosum express the phagocytic marker CD11b and are responsible for the phagocytosis of myelin debris (53,54). This supportive action of MPs is an essential step for subsequent remyelination at W6 and W6 + W6 recovery (49,55).…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by removing myelin debris, thus permitting entry of oligodendrocyte precursor cells. Phagocytosing myeloid cells are also implicated as sources of molecular signals that attract and support the differentiation of the oligodendrocyte precursor cells (45,46). Understanding and potentially manipulating the phagocytic clearance of myelin has clear consequences for MS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, myelin debris may contain inhibitory molecules that antagonize axonal regeneration (45), and the removal of axonal debris by microglia increases axonal regeneration (46,47). Additionally, microglial phagocytosis of myelin debris can promote resolution of the CNS inflammatory response (16,48), and myelin-phagocytosing microglia express genes involved in the activation, migration, proliferation, and differentiation of oligodendrocyte precursor cells (49). Recently, it has been shown that if CNS-resident microglia cannot clear degenerated myelin from affected axons, remyelination is impaired, whereas infiltrating macrophages did not contribute to this function (50).…”
Section: Discussionmentioning
confidence: 99%